Lung segmentectomy: does it offer a real functional benefit over lobectomy?. (25th October 2017) - Charloux, Anne; Quoix, Elisabeth
Anatomical segmentectomy has been developed to offer better pulmonary function preservation than lobectomy, in stage IA lung cancer. Despite the retrospective nature of most of the studies and the lack of randomised studies, a substantial body of literature today allows us to evaluate to what extent lung function decreases after segmentectomy and whether segmentectomy offers a real functional benefit over lobectomy. From the available series, it emerges that the mean decrease in forced expiratory volume in 1 s (FEV1 ) is low, ranging from −9% to −24% of the initial value within 2 months and −3 to −13% 12 months after segmentectomy. This reduction in lung function is significantly lower than that induced by lobectomy, but saves only a few per cent of pre-operative FEV1 . Moreover, the published results do not firmly establish the functional benefit of segmentectomy over lobectomy in patients with poor lung function. Some issues remain to be addressed, including whether video-assisted thoracic surgery (VATS) segmentectomy may preserve lung function better than VATS lobectomy in patients with poor lung function, especially within the early days after surgery, and whether this may translate to lowering the functional limit for surgery. Eventually, trials comparing stereotactic ablative body radiotherapy, radiofrequency ablation and segmentectomy functional consequences are warranted. Lung segmentectomy offers mild post-operative to small long-term functional benefits over lobectomy http://ow.ly/dcPQ30fuCU9